Recruitment and baseline characteristics of participants in the AgeWell.de study: a pragmatic cluster-randomized controlled lifestyle trial against cognitive decline - Röhr, Susanne; Zülke, Andrea; Luppa, Melanie; Brettschneider, Christian; Weißenborn, Marina; Kühne, Flora; Zöllinger, Isabel; Samos, Franziska-Antonia Zora; Bauer, Alexander; Döhring, Juliane; Krebs-Hein, Kerstin; Oey, Anke; et al. (International journal of environmental research and public health, 2021)
AgeWell.de; dementia; cognitive function; prevention; intervention; lifestyle; trial; RCT; cluster-randomized controlled trial; primary care; general practitioner
Gesehen am 09.03.2021